The Effect of the Proportion of Female Board of Directors on Firm Performance in All Companies Listed on the Indonesian Stock Exchange with Innovation as a Mediating Variable - Christiawan, Yulius Jogi; Simon, Jessica Wijaya; Teng, Theresya Krismenda (Journal of International Conference Proceedings, 2023)
The study investigates the relationship between the proportion of female directors on corporate boards and firm performance, with innovation serving as a mediating variable. Previous research has revealed inconsistencies between those variables. Therefore, this study investigates whether there is a direct and indirect effect of the proportion of female directors on firm performance, which is innovation as a mediating variable. To measure the variables studied, this study also employs quantitative data types and secondary data sources from 55 companies listed on the Indonesian Stock Exchange from 2017 to 2021. Using the Partial Least Square method, the following findings were obtained: (1) The proportion of women on the board of directors has no direct impact on firm performance. (2) Female on board of directors has a positive significant impact on innovation, (3) This research shows a positive significant relationship between innovation and firm performance, and (4) The results also show full mediation of innovation on the impact of proportion of female on board of directors on firm performance. Since it is being conducted in Indonesia, it may differ in other countries, and further research such as using the difference mediating variables and indicators to influence the study's results is strongly advised.Â Keywords: Female Directors, Firm Performance, Innovation, Partial Least Squares, Indonesia Stock Exchange